Influence of technological variables on the functionality of the cell-free supernantant of fermented buttermilk - Peteán, Melina (2014)
Buttermilk is a suitable substrate for fermentation with proteolytic strains of Lactobacillus in order to release peptide fractions able to enhance the gut mucosal immune system. We aimed to determine the influence of the degree of proteolysis of buttermilkproteins on their functionality. Animals received for 7 consecutive days the cell-freefraction of 10 or 20% (w/v) buttermilk fermented with Lactobacillus delbrueckii subsp.lactis 210 at pH 6 contant. pH was controlled either with NaOH or Ca(OH)2. No significant differences in the number of IgA-producing cells in the small intestine of mice were found.The functional capacity of the product under study was not affected by the technologicalvariables considered.